Normative Analysis of the Implementation of Murabahah Contracts in Consumer Financing at Islamic Banks - Dini Marissa; Budi Abdullah (Dinasti Research, 2026)
Islamic banking in Indonesia has shown rapid growth, with murabahah contracts emerging as the dominant financing instrument, accounting for more than 60% of the total financing portfolio. Murabahah is preferred due to its simplicity and relatively low risk. However, its implementation in practice often deviates from normative provisions. Key issues include a lack of transparency in profit margins, the bundling of additional costs, and weak real ownership of goods by the bank. This study aims to analyze the application of murabahah contracts in consumer financing within Islamic banks from the perspective of positive law and the principles of fiqh muamalah. The research employs a normative juridical method, using primary legal sources (Law No. 21 of 2008, DSN-MUI Fatwa No. 04/2000, and PSAK Syariah No. 102), secondary legal materials (fiqh muamalah literature and Sinta 2/3 indexed journals), and tertiary materials. The analysis is conducted through statutory, conceptual, and comparative approaches. The findings indicate a gap between regulation and practice: banks often do not bear the risks associated with ownership of goods, causing murabahah contracts to lose their fundamental nature as sale-and-purchase agreements and resemble conventional credit schemes. The legal implications extend beyond maladministration to potential violations of sharia principles, which may render the contract fasid (defective). This study recommends strengthening murabahah governance through ownership audits and enhanced margin transparency, so that murabahah practices can better reflect maqasid al-shariah and improve public trust in Islamic banking.